A New Approach for Prediction of Surface Tension of Binary Liquid Mixture - Saxena, M.C. (Asian Journal of Chemistry, 2010)
Surface tensions of three binary liquid mixtures of hexane-decane, hexadecane-decane at 30ºC and benzene-carbon tetrachloride at 50ºC have been predicted by a new approach, using surface tension of pure components. Results obtained have been compared with that obtained from Brock and Bird relation and Eberhart relation. Relative merits and limitations of all the relations have been assessed.